2018
DOI: 10.1007/s00280-018-3569-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival impact of post-progression chemotherapy in advanced gastric cancer: systematic review and meta-analysis

Abstract: Post-Cx% both after 1st-Cx and 2nd-Cx were correlated with mOS/mPPS, suggesting a survival benefit of 3rd-Cx in addition to that of 2nd-Cx for AGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Little is understood about the prognostic impact of subsequent therapeutic intervention after discontinuation of immunotherapy. However, a systematic review and metaanalysis demonstrated that post-progression subsequent chemotherapy after both first-line and secondline regimens was significantly associated with longer OS in patients with advanced gastric cancer [17]. This meta-analysis recommended third-line chemotherapy after second-line chemotherapy to improve the prognosis [17].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Little is understood about the prognostic impact of subsequent therapeutic intervention after discontinuation of immunotherapy. However, a systematic review and metaanalysis demonstrated that post-progression subsequent chemotherapy after both first-line and secondline regimens was significantly associated with longer OS in patients with advanced gastric cancer [17]. This meta-analysis recommended third-line chemotherapy after second-line chemotherapy to improve the prognosis [17].…”
Section: Discussionmentioning
confidence: 94%
“…However, a systematic review and metaanalysis demonstrated that post-progression subsequent chemotherapy after both first-line and secondline regimens was significantly associated with longer OS in patients with advanced gastric cancer [17]. This meta-analysis recommended third-line chemotherapy after second-line chemotherapy to improve the prognosis [17]. Accordingly, post-progression salvage chemotherapy after nivolumab may have a survival benefit as a fourth-line treatment.…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review with a meta-analysis showed the proportion of patients receiving postprogression chemotherapy correlated with the postprogression survival and the OS both for first-and secondline chemotherapy [43]. In a limited survival time for the recurrent gastric cancer patients, appropriate use with a limited number of effective drugs is essential to improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…Second-line chemotherapy for AGC is provided more frequently in Japan than in other countries, as shown by a high proportion of patients (approximately 75%-80%) receiving second-line chemotherapy in several Japanese phase III trials [2,4,12]. Second-line chemotherapy is effective in prolonging the survival time of patients [14]. As shown in the RAINBOW trial, the combination therapy of paclitaxel and ramucirumab, which targets vascular endothelial growth factor receptor-2, has been established as a new standard second-line treatment for AGC [5].…”
Section: Discussionmentioning
confidence: 99%